A EMPIRICAL STUDY ON SHIFT IN ONLINE CONSUMER BUYING BEHAVIOUR FROM TRADITIONAL MARKETS - Mr.G. Madan, Dr.Murugan Ramu (International Journal of Advanced Science and Technology, 2020)
The fundamental reason for this examination is to look at the components influencing the online shopping conduct of Net-age contrasting and pre Net-age. To do as such, the examination builds up an exploration demonstrate including nine autonomous factors that are speculated to anticipate the aim of procurement utilizing the online shopping setting and Net-geners' attributes. The research design is exploratory and experimental. It explored the problem tested with hypothesis and provide the solution from the analysis. Convenience sampling method is used (Non probability sampling).  The sample size is 1500. The data is refrained finally as 1442. Data is collected through the primary and secondary sources. Questionnaire is used as the primary data collection and the articles, journals, reports, newsletters are considered as the secondary sources. The analysis is done by using SPSS 21 version. The analysis is carried out for demographic statistics (Gender, Age, Status, Education and Occupation) and hypothesis testing correlation and cross tabulation is used. The results hence received is that online shopping will one day supersede traditional shopping methods as seen in the data collected from the survey conducted, reasons for such a shift include convenience, speed in delivery, cost differences, consumer preferences etc. One of the main markets that are still traditionally used by consumers is the perishable markets such as vegetables,fruits and dairy products etc, which won’t last the long journey from warehouses to the delivery areas hence making it a product that people tend to shop for in traditional markets.